2013
DOI: 10.1371/journal.pone.0075861
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatory Effect of the Stable Vasoactive Intestinal Peptide Analog RO 25-1553 in Murine and Rat Lungs

Abstract: RationaleStable analogs of vasoactive intestinal peptide (VIP) have been proposed as novel line of therapy in chronic obstructive pulmonary disease (COPD) based on their bronchodilatory and anti-inflammatory effects. We speculated that VIP analogs may provide additional benefits in that they exert vasodilatory properties in the lung, and tested this hypothesis in both ex vivo and in vivo models.MethodsIn isolated perfused mouse lungs and in an in vivo rat model, pulmonary blood vessels were preconstricted by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 75 publications
2
6
0
Order By: Relevance
“…Sphingolipids thus exert a dual action on TRPC6 in HPV, in that they both translocate (nSMase-derived ceramide) and activate (S1P) TRPC6 channels. CFTR inhibition or deficiency had no effect on basal perfusion pressures in the isolated lung, a finding that is in line with the virtual lack of basal vascular tone in this preparation (36). However, both interventions markedly reduced the HPV response in isolated mouse lungs.…”
Section: Discussionsupporting
confidence: 78%
“…Sphingolipids thus exert a dual action on TRPC6 in HPV, in that they both translocate (nSMase-derived ceramide) and activate (S1P) TRPC6 channels. CFTR inhibition or deficiency had no effect on basal perfusion pressures in the isolated lung, a finding that is in line with the virtual lack of basal vascular tone in this preparation (36). However, both interventions markedly reduced the HPV response in isolated mouse lungs.…”
Section: Discussionsupporting
confidence: 78%
“…In our present study, the pulmonary vasodilative properties of VIP were preserved after its inhalation. This is in line with a recent study of Yin et al (33), who demonstrated that inhalation of a stable analog of VIP antagonizes acute hypoxic pulmonary vasoconstriction in an intact rat model.…”
Section: Discussionsupporting
confidence: 92%
“…This is comparable to previous data using a peptide preparation in this model (14) and discloses the difficulties that have to be taken into account when aerosolizing peptides to the lung. Therefore, stable analogs of VIP or liposomal-packed VIP have been suggested to prolong the biological activity of VIP when used as an aerosol (17,30,33).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we did not observe increased VIP serum levels in COPD patients with PAH and did not find a correlation of VIP serum levels with low oxygen saturation as suggested by animal studies and in vitro models [45][46][47] . It is difficult to explain this discrepancy between studies in animal and human beings, as it may not necessarily be reproducible in COPD patients.…”
Section: Discussionmentioning
confidence: 74%